Host subspecific viral strains in European house mice: Murine cytomegalovirus in the Eastern (Mus musculus musculus) and Western house mouse (Mus musculus domesticus) - Čížková, Dagmar; Baird, Stuart J E; Těšíková, Jana; Voigt, Sebastian; Ľudovít, Ďureje; Piálek, Jaroslav; Goüy de Bellocq, Joëlle (Virology, 2018)
Murine cytomegalovirus (MCMV) has been reported from house mice (Mus musculus) worldwide, but only recently from Eastern house mice (M. m. musculus), of particular interest because they form a semi-permeable species barrier in Europe with Western house mice, M. m. domesticus. Here we report genome sequences of EastMCMV (from Eastern mice), and set these in the context of MCMV genomes from genus Mus hosts. We show EastMCMV and WestMCMV are genetically distinct. Phylogeny splitting analyses show a genome wide (94%) pattern consistent with no West-East introgression, the major exception (3.8%) being a genome-terminal region of duplicated genes involved in host immune system evasion. As expected from its function, this is a region of maintenance of ancestral polymorphism: The lack of clear splitting signal cannot be interpreted as evidence of introgression. The EastMCMV genome sequences reported here can therefore serve as a well-described resource for exploration of murid MCMV diversity.
Keywords: Animals; Genome, Viral; Europe; Geography; Immune Evasion; genom virový; Evropa; Mice; zeměpis; myši; Host Specificity; Genetic Variation; Phylogeny; polymorfismus genetický; imunitní únik; zvířata; Muromegalovirus; fylogeneze; genetická variace; Polymorphism, Genetic; hostitelská specificita